Село і місто, або як конструюються культурні кордони - Полек, Т. (Місто: історія, культура, суспільство, 2019)
У статті розглядаються механізми конструювання культурних кордонів між сільськими і міськими поселеннями. На основі проведеного історіографічного аналізу озвучено підходи до розуміння означення понять «місто» та «село», а також недоліки і переваги їхнього дихотомічного прочитання. З огляду на особливості проживання в поселеннях з різною кількістю, щільністю і різнорідністю населення було проаналізовано ті норми соціальної взаємодії, які формують сільський і міський спосіб життя. Зокрема, простежено залежність конструювання уявлень про спосіб життя від міського і сільського дискурсів, а також вплив романтизму та прагматизму на формування узвичаєних повсякденних практик. Ключові слова: місто, село, конструкціонізм, дискурс-аналіз. The article deals with the mechanisms of construction of cultural boundaries between rural and urban settlements. Historiographical analysis helped to outline the approaches to understanding the definition of the concepts of “city” and “village”, as well as disadvantages and advantages of their dichotomous reading. At the same time, economic conditions of modern world stimulate eroding even the most general boundaries between urban and rural because of changing the whole system of agricultural production, globalisation and urbanisation processes. Considering of social interaction norms, which form the rural and urban lifestyle, helped to analyze the peculiarities of settling in settlements with different numbers, density and heterogeneity of the population. So the dependence of constructing lifestyle representations on urban and rural discourses, as well as the influence of romanticism and pragmatism on the formation of customary everyday practices, was traced in this research. Thus, urbanism shows the importance of the anonymity of daily contacts, which is an element of urban discourse associated with categories of diversity, opportunities and temptations. On the other hand, rural discourse appeals to the value of traditions, for example the customs of neighboring mutual assistance, which are regulated in peasant communities. Such customs, despite their romantic halo, actually have an economic foundation, which could be reduced to a pragmatic way of obtaining goods and services in a limited resource by attracting accessible social networks in the form of neighbors and relatives.